In vitro antioxidant and antimicrobial activity of some Lamiaceae species - Albayrak, Sevil; Aksoy, Ahmet; Albayrak, Songul; Sagdic, Osman (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
The methanolic extracts, infusions, decoctions and hydrosols of six plants were investigated for their total phenolic contents, antioxidant and antimicrobial activities: Mentha piperita (Peppermint), Thymus vulgaris (thyme), Melissa officinalis (lemon balm), Ocimum basilicum (basil), Rosmarinus officinalis (rosemary) and Salvia officinalis (sage) (Lamiaceae). Total phenolic contents were determined by Folin-Ciocalteu procedure and ranged from 111.03 +/- 0.6 (sage methanolic extract) to 19.07 +/- 0.0 mg (basil methanolic extract) gallic acid equivalent /g extract. The antioxidant activity was evaluated by two methods, DPPH and phosphomolybdenum assays. The decoction of rosemary showed the highest DPPH radical scavenging activity (IC50 = 8.36 mu g/mL). The methanolic extract of Peppermint showed the highest total antioxidant activity (241.85 +/- 1.9 mg ascorbic acid equivalent /g extract) measured by phosphomolybdenum assay. The antimicrobial activities of herbs were tested against eight bacteria and two yeasts.
Keywords: Antimicrobial activity; antioxidant activity; DPPH; Lamiaceae; phenolics; PLANT-EXTRACTS; CAPACITY; HERBS; TEA; INFUSIONS; RADICALS; OREGANO; THYME; L.; Science & Technology - Other Topics